UTILIZING GAMIFIED QUIZZES TO ENHANCE STUDENTS' ENGLISH READING COMPREHENSION SKILLS - Salim, Malik; Sukarno, Karisman Muhammad; Robbaniyah, Inayatur; Aminudin, Muhamad Fauzan; Widyastuti, Sri Harti; Bariyyah, Khoirul; Hidayati, Anni Nurul (Universitas Labuhanbatu, 2025)
Purpose – Reading comprehension includes identifying key concepts, drawing conclusions, and critically engaging with written resources, all of which are integral to academic success and communication. However, disinterest, insufficient vocabulary and an inclination toward technology have hindered students' reading growth. This study investigates the effectiveness of gamified quizzes, explicitly using the Quizizz application, in enhancing reading comprehension among junior high school students. Methodology – Employing a quasi-experimental design with a one-group pretest-posttest framework, the study was conducted with Class VII-A students at SMP 1 Yogyakarta during the 2024/2025 academic year. The data were analyzed using SPSS version 25. Findings – Descriptive statistics of pretest and posttest scores have indicated an enhancement in students' reading comprehension, with the average moving from 58.33 to 79.53. The results underscore the capacity of gamified quizzes to enhance engagement, motivation, and literacy abilities, presenting a viable solution to modern issues in reading instruction.Significance – Future study should investigate the broader applications of gamified technologies and their persistent impact on learning outcomes.Keywords: Reading; reading comprehension; quizzes application